SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN BAYAM MERAH HIDROPONIK DAN KONVENSIONAL - Saputri, Romadhiyana Kisno; Pitaloka, Ria Indah Kusuma; Ardianti, Aprillia Dwi; Nisak, Siti Khoirun; Ni'am, Musfirotun; Farlina, Nur; Afifta, Siti Nur (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2025)
Antioxidants are compounds that have the ability to againts the harmful effects of free radicals. Antioxidant activity was influenced by active compounds, growing environment, cultivation systems, techniques and handling of raw materials. Hydroponics is a plant cultivation system that does not use soil as media. Differences in hydroponic and conventional systems in soil use can affect antioxidant activity. This study aims to conduct a qualitative test of antioxidants through phytochemical screening and analysis of thin layer chromatography (TLC) and to test the antioxidant activity of hydroponic and conventional red spinach leaf extract. Red spinach leaves were extracted by maceration method for 3 days with stirring every 1x24 hours. The red spinach leaf extract was then organoleptically tested for color, shape, and odor. Phytochemical screening was carried out to determine the content of flavonoids and saponins using color and foam reactions. The screening results were confirmed by thin layer chromatography (TLC) analysis with hexane:ethyl acetate as the mobile phase in a ratio of 5:5. Antioxidant activity test with DPPH Method. The results of the calculation of the yield on hydroponic red spinach leaf extract was 11.5% and conventional was 15.1%. The results of phytochemical screening and TLC analysis showed that both hydroponic and conventional red spinach leaf extracts were positive for flavonoid and saponin compounds. The IC50 value of hydroponic red spinach leaf extract was 142.31 while conventional was 73.73 ppm. The antioxidant activity of hydroponic red spinach leaf extract was in the medium category and conventional in the strong category.